Differences in pharmacology of tumor necrosis factor (TNF) antagonists - S. Bombardieri; U. Fiocco (PAGEPress Publications, 2011)
The commercially available inhibitors of TNF are constituted by two classes of molecules: the soluble receptors (Etanercept: Amgen Inc. Wyeth) and the monoclonal antibodies (Adalimumab: Abbott Laboratories and Infliximab: Centocor, Inc.). The differences in their molecular structure, mechanism of action, pharmacokinetics (PK) and pharmacodynamics (PD) are discussed, along with the differences concerning dose, administration regimens, drug concentrations and pharmacological interactions. In order to explain the clinical differences observed when these agents are used in the "real world", which can arise from the respective PK characteristics (kinetics, route and frequency of administration, type of TNF binding, effects on cytokines) and PD responses and peculiar mechanisms of action, with distinctive immune function (LFTa inactivation; apoptosis induction, TNF immunoprecipitation, C1q binding and CDC induction; Fcg cross-linking and ADCC induction), the dynamics of interaction of the two classes of neutralizing molecules with TNF, and the ability in restoring TNF homeostasis, are outlined.